E-WASBAHA : a mobile application for flood monitoring in Metro Manila using crowdsourcing - Balceda, Charlene D.; San Juan, Raynus Eleasar Q.;Tumamak, Jhonesa R.;Velasquez, Jr., Reynaldo E. (Manila : National University, 2017)
E-WASBAHA is a mobile application that aims to give flood information to users in Metro Manila using crowdsourcing. Nowadays, commuters are using social media and mobile applications to be updated of the flood and to locate the places that are non-passable.
Title page -- Recommendation for oral examination -- Approval sheet -- English editing certificate -- Dedication -- Acknowledgement -- Executive summary -- Publishable full paper format -- Table of contents -- List of figures -- List of tables -- Chapter I. Introduction -- Chapter II. Review of related literature and studies -- Chapter III. Technical background -- Chapter IV. Methodology, results and discussions -- Chapter V. Summary and recommendations.
Includes bibliographical references.